Symmetric properties of positive solutions for fully nonlinear nonlocal system. (October 2019) - Wang, Pengyan; Niu, Pengcheng
Abstract: In this paper we obtain symmetry and monotonicity of positive solutions for the systems involving fully nonlinear nonlocal operators in a domain (bounded or unbounded) in R n via using a direct method of moving planes. This extends the results in Wang and Niu (2017) and also is the first result of the symmetry for a fully nonlinear nonlocal system containing gradient terms with different order.